2018
DOI: 10.17116/hirurgia2018875
|View full text |Cite
|
Sign up to set email alerts
|

Valve sparing aortic root replacement (David Procedure) in 36 year - old woman with the Marfan syndrome at the 27th week of pregnancy

Abstract: The article presents a clinical case of valve sparing aortic root replacement (David Procedure) in 36 year - old woman with the Marfan syndrome at the 27th week of gestation followed by successful prolongation of pregnancy. Indications for reconstructive intervention with cardiopulmonary bypass were: severe aortic valve insufficiency, Sinus of Valsalva Aneurysm (66 mm) and the ascending aorta dilatation (53 mm) with a rapid increase of aortic root dimension (12 mm during 9 weeks). The patient underwent a valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have confirmed the safety and efficacy of valve-sparing operations in selected patients. 3,[19][20][21] A recently published systemic review emphasized the advantages of the valve-sparing procedure in MFS patients. Its long-and short-term results included lower in-hospital, longterm mortality, and lower valve-related reintervention rates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed the safety and efficacy of valve-sparing operations in selected patients. 3,[19][20][21] A recently published systemic review emphasized the advantages of the valve-sparing procedure in MFS patients. Its long-and short-term results included lower in-hospital, longterm mortality, and lower valve-related reintervention rates.…”
Section: Discussionmentioning
confidence: 99%